Smoke-Free Air Interventions in Seven Latin American Countries: Health and Financial Impact to Inform Evidence-Based Policy Implementation. Issue 12 (22nd July 2020) - Bardach, Ariel; Rodríguez, María Belén; Ciapponi, Agustín; Augustovski, Federico; Andrea, Alcaraz; Soto, Natalie; Virgilio, Sacha; Reynales-Shigematsu, Luz Myriam; Roberti, Javier; Pichón-Riviere, Andrés
Abstract: Introduction: Disease burden due to tobacco smoking in Latin America remains very high. The objective of this study was to evaluate the potential impact of implementing smoke-free air interventions on health and cost outcomes in Argentina, Bolivia, Brazil, Chile, Colombia, Mexico, and Peru, using a mathematical model. Aims and Methods: We built a probabilistic Monte Carlo microsimulation model, considering natural history, direct health system costs, and quality of life impairment associated with main tobacco-related diseases. We followed individuals in hypothetical cohorts and calculated health outcomes on an annual basis to obtain aggregated 10-year population health outcomes (deaths and events) and costs. To populate the model, we completed an overview and systematic review of the literature. Also, we calibrated the model comparing the predicted disease-specific mortality rates with those coming from local national statistics. Results: With current policies, for the next 10 years, a total of 137 121 deaths and 917 210 events could be averted, adding 3.84 million years of healthy life and saving USD 9.2 billion in these seven countries. If countries fully implemented smoke-free air strategies, it would be possible to avert nearly 180 000 premature deaths and 1.2 million events, adding 5 million healthy years of life and saving USD 13.1 billion in direct healthcare. Conclusions: Implementing the smoke-free air strategy would substantially reduce deaths, diseases, and health care costs attributed to smoking. Latin American countries should not delay the full implementation of this strategy. Implications: Tobacco smoking is the single most preventable and premature mortality cause in the world. The Framework Convention on Tobacco Control, supported by the World Health Organization, introduced a package of evidence-based measures for tobacco control. This study adds quality evidence on the potential health effects and savings of implementing smoke-free air policies in countries representing almost 80% of the Latin America and the Caribbean population.